STEAM makers : fostering creativity and innovation in the elementary classroom - Maslyk, Jacie, ....- (Thousand Oaks : Corwin, 2016)
Go beyond theory and learn how to systematically integrate STEAM and Maker spaces that prepare students for real-world experiences. This engaging resource outlines step-by-step processes to help anyone start their STEAM and Maker journey. Includes charts, checklists, web links, and profiles to help you make meaningful subject area connections and tap your students' natural curiosity.
Includes bibliographical references and index.
Keywords: Education, Elementary -- Activity programs; Creative activities and seat work; Arts -- Study and teaching (Elementary).; Science -- Study and teaching (Elementary).; Interdisciplinary approach to education